Nuthatches vary their alarm calls based upon the source of the eavesdropped signals - Nora V Carlson (Nature Portfolio, 2020)
Animals can obtain information on predation risk directly from observing predators or indirectly from the alarm calls of others. Here, the authors show that red-breasted nuthatches encode information on risk in their own alarm calls differently depending on the source of the information.